APLIKASI GA3 DALAM MEMECAHKAN DORMANSI BIJI Picrasma javanica SETELAH PENYIMPANAN PADA BERBAGAI SUHU SIMPAN - Ning Wikan Utami (Jurnal Teknologi Lingkungan, 2010)
Picrasma javanica is one of the medicinal plants that has an anti malaria potency,it is belonging into Simaroebaceae family. The aim of this research is to know the effect of GA3 on broken dormancy of P. Javanica seed after storaged in the various temperature to enhance and increased seed germination. The experiment was carried out in the Macropropagation Laboratory, Cibinong Science Center, Research Center for Biology,LIPI, using a Complete Randomized Design with two factors in three replication.The first factor is condition of storage i.e room (28 ± 10 C, RH 80%), incubator (200 C,RH 90%), incubator ( 50 C, RH 95%) dan deep freezer (- 200 C, RH ). The second factor is long of storage i.e. 1,2,3,4,5 and 5 months. GA3 100 ppm was used for broken seeddormancy. The result showed that there was no interaction between temperature and long of storage. GA3 solution can be broken on seed dormancy before and after storage in the various temperature excepted in deep freezer ( – 200 C, RH 65%), there are no seed germinate since 1 month storage. P. javanica seed that storage in incubator 50 C is the best method and after 5 months the germination percentage is still high (73,3%) with GA3 but only 18,33% without GA3. On the other treatments the germination percentage is less than 50%. The highest germination value (14,1) that was recorded in the seeds that storage in incubator (200 C, RH. 95%).Key words: GA3, dormancy, temperature, long of storage, seed , P. javanica